2015
DOI: 10.1097/ccm.0000000000001143
|View full text |Cite
|
Sign up to set email alerts
|

Open Lung in Lateral Decubitus With Differential Selective Positive End-Expiratory Pressure in an Experimental Model of Early Acute Respiratory Distress Syndrome*

Abstract: After maximum lung recruitment, lateral decubitus and differential lung ventilation enabled the titration of optimum-selective positive end-expiratory pressure values for the dependent and the nondependent lungs, made possible the application of an optimized regional open lung approach, promoted better aeration distribution, and minimized lung tissue inhomogeneities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…An increasing amount of data in literature suggests that driving pressure is a predictor of mortality in ARDS patients [ 44 , 45 ], and a key mediator of the effects of various ventilatory interventions [ 5 , 6 , 15 ]. ΔP is the tidal change in static trans-respiratory pressure, measured as P PlatRS -PEEP tot , in response to a volume-controlled breath and expresses the ratio between Vt and respiratory system compliance Vt/C RS [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of data in literature suggests that driving pressure is a predictor of mortality in ARDS patients [ 44 , 45 ], and a key mediator of the effects of various ventilatory interventions [ 5 , 6 , 15 ]. ΔP is the tidal change in static trans-respiratory pressure, measured as P PlatRS -PEEP tot , in response to a volume-controlled breath and expresses the ratio between Vt and respiratory system compliance Vt/C RS [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…During one-lung ventilation (OLV) in the lateral decubitus position for thoracic surgery, hypoxemia may occur in almost 10% of patients [ 1 3 ], due to the total collapse of the non-dependent lung and, eventually, to atelectasis in the ventilated, dependent lung [ 4 , 5 ]. We recently demonstrated [ 6 ] that a recruitment strategy applied to the dependent lung followed by a moderate PEEP level results in significant alveolar recruitment, increased arterial oxygenation and reduction of the respiratory system elastance (E RS ), without hemodynamic impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Ventilating independently different parts of the lung with different pressures may help force the air into atalectatic parts, reduce V/Q mismatch and improve oxygenation [14, 15]. This theory is supported by experimental models [7, 12]. Clinical trials showed a similar beneficial effect of DLV in patients in intensive care units [1618] and during open thoracic surgery [9, 19].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study is to compare ventilation modalities during OLV, which may improve oxygenation with minimal impairment of the surgical field conditions. In this study, the non-dependent lung was ventilated alternately, in crossover fashion, by CPAP and by a portable ventilator with low rate and pressure in a DLV technique [79]. We anticipated that a low ventilation rate and pressure would produce the least interference with the surgeon’s exposure and, at the same time, improve oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…This is hardly possible in a supine or prone patient but the lateral position may enable separation of upper and lower lung regions since the non-dependent and the dependent lungs can be ventilated separately with a double lumen endobronchial catheter. Considerable improvement of gas exchange and morphology by reducing or eliminating atelectasis with no over-distention of other lung regions has been achieved both in animal experiments and in clinical studies (14,15 In order to limit over-distension of lung regions, a low tidal volume should be applied so that the driving pressure is kept as low as possible. Techniques to apply airway pressures individually in proportion to regional lung mechanical properties would allow more homogeneous aeration and distribution of ventilation and blood flow.…”
Section: Mert şEntürk Editormentioning
confidence: 99%